Rheological Properties of Cement-Modified Asphalt Binders - Al-Khateeb, Ghazi; Ghuzlan, Khalid; Ismail, Mohammed; Shabib, Ahmad; Naeem, Marwan; Elbaz, Yousef (Frontiers in Built Environment, 2022)
Asphalt pavements are subjected to major distresses like fatigue, rutting, and low-temperature cracking due to repeated traffic loading and climatic conditions. The modification of asphalt binder (major component of asphalt paving mixture) by using additives helps in minimizing the possibility for pavement distresses to occur. The cement additive was used in this study at cement-to-asphalt (C/A) percentages of 0, 10 and 20% by volume. The main objective of the study was to investigate the impact of C/A percentage, temperature, and loading frequency on rutting resistance of asphalt binders using statistical analysis. Two aging conditions were also used: unaged condition and short-term aging condition in the Rolling Thin-Film Oven (RTFO). The Dynamic Shear Rheometer (DSR) test was used to characterize the asphalt binders at ten loading frequencies (0.1, 0.3, 0.6, 1, 1.59, 3, 5, 7, 8, and 10 Hz) and four temperatures (58, 64, 70, and 76C). These combinations were used to cover a wide range of combined conditions and to follow the high-temperature range for the Superpave performance grade (PG) system. Multiple statistical analysis (one-way analysis of variance (ANOVA) and correlation tests) were performed to identify the relation between the tested variables and the rutting parameter (G*/sin). Regression analysis was conducted to depict an accurate model that can predict the rutting parameter (G*/sin) for each aging condition. The ANOVA test results showed that the cement addition (represented by the C/A percentage) had a significant impact on the rutting parameter of cement-modified asphalt (CMA) binders for both aging groups. Furthermore, the correlation test conducted proved that changing both the temperature and the C/A percentage had significant effects on the rutting parameter. Finally, regression analysis was conducted to develop four models that predict the rutting parameters for unmodified and modified binders for both unaged and aged samples, all with significantly high R2-values.